2019
DOI: 10.1001/jamapediatrics.2019.1658
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sexting With Sexual Behaviors and Mental Health Among Adolescents

Abstract: IMPORTANCE Sexting is the exchange of sexual messages, photographs, or videos via technological devices and is common and increasing among youth. Although various studies have examined the association between sexting, sexual behaviors, and mental health, results are mixed. OBJECTIVE To provide a meta-analytic synthesis of studies examining the associations between sexting, sexual behavior, and mental health using sex, age, publication date, and study methodological quality as moderators. DATA SOURCES Electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
150
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(167 citation statements)
references
References 66 publications
11
150
1
5
Order By: Relevance
“…Criterion validity was supported by relations between A-SextS and different variables in the available literature. This was the case for age, sexual activity, and pornography consumption, which have consistently been found to positively correlate with sexting [2,18,19]. Nine different subscales of A-SextS were also defined according to sexting action and addressees: sending sexts to a boy/girlfriend (SF), sending sexts to someone known in person (SK), sending sexts to someone known only on internet (SI), posting or live-streaming pictographic content (PS), asking for sexts from a boy/girlfriend (AF), asking for sexts from someone known in person (AK), asking for sexts from someone only known on the internet (AI), receiving sexts (R), and refusing to send sexts (RS).…”
Section: Stage 2: Concurrent and Criterion Validitymentioning
confidence: 73%
See 1 more Smart Citation
“…Criterion validity was supported by relations between A-SextS and different variables in the available literature. This was the case for age, sexual activity, and pornography consumption, which have consistently been found to positively correlate with sexting [2,18,19]. Nine different subscales of A-SextS were also defined according to sexting action and addressees: sending sexts to a boy/girlfriend (SF), sending sexts to someone known in person (SK), sending sexts to someone known only on internet (SI), posting or live-streaming pictographic content (PS), asking for sexts from a boy/girlfriend (AF), asking for sexts from someone known in person (AK), asking for sexts from someone only known on the internet (AI), receiving sexts (R), and refusing to send sexts (RS).…”
Section: Stage 2: Concurrent and Criterion Validitymentioning
confidence: 73%
“…In an ongoing meta-analysis it has also been observed that such rates have been progressively increasing over the last ten years (e.g., 7%, 95% CI: 5%, 10% for sending sexts in studies collecting data in 2009, versus 16%, 95% CI: 13%, 20% in 2014, and 29%, 95% CI: 20%, 39% in 2018) [17]. The most supported findings concerning correlates have suggested that sexting is more prevalent with increasing age [2], and is significantly related to adolescent sexual behavior, such as having actual sexual intercourse, and to other online and offline sexual experiences, such as pornography consumption [18,19]. The disparate findings in sexting research may be due to differences in how the practice has been conceptualized and measured among the various studies [2,3,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the mixed findings and predominantly cross-sectional nature of the existing research on sexting-which is reflected in a recent call for more longitudinal research (Mori et al, 2019)-and the need for greater focus on outcomes specific to young women, the current study sought to longitudinally explore links between adolescent girls' sexting and psychological well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Because sexting was initially largely conceptualized as a potentially risky behavior among emerging adults, much of the existing research has focused on the association between sexting and a range of risk factors, including unprotected sex, STI diagnosis, substance use, sexual coercion, pornography use, risky internet use, and psychological distress [ 1 , 3 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. An additional area of concern related to sexting is the potential for coercion and aggression in interpersonal relationships that this behavior may afford.…”
Section: Introductionmentioning
confidence: 99%